Protection of patient data privacy on IoT devices for healthcare in the era of smart cities: a health law perspective - Naili, Yuris Tri; Afrilies, Marlia Hafny; Garunja, Evis; Purwono, Purwono (Universitas Ahmad Dahlan, 2024)
Introduction to the Problem: The Internet of Things (IoT) has enabled the use of medical devices in the healthcare sector while presenting challenges in regard to the security and privacy of patients’ medical data. This article conducts a systematic literature review to evaluate the existing regulations related to the security and privacy of the patient’s medical data in real-time data collection through IoT in the context of a Smart City.Purpose/Study Objectives: This study aims to identify gaps in the existing regulations, analyze the implementation of these regulations in practice, and evaluate the impact of IoT technology on the privacy and security rights of patients’ medical information in the healthcare sector.Design/Methodology/Approach: The research employed a systematic literature review, by analyzing relevant articles, legal documents, and regulations. Data were examined from a case study of the implementation of IoT devices for healthcare in Smart Cities as well as interviews with legal experts in the field of healthcare services.Findings: The existence of the Electronic Information and Transaction Law, Personal Data Protection Law, and the latest Health Law provides the initial regulatory foundation for ensuring the security of personal data in the integrated governance of Smart Cities, especially in telemedicine services. Implementing regulations for these laws are necessary to technically accommodate the needs for the security of the patients’ data, ensuring that there is no imbalance between the provisions of the laws that are enacted and their implementation in the community.Paper Type: Research Article